Screening and Identification of Two Human Intestinal Strains Metabolizing Caffeic Acid and Exploring Their Metabolic Processes - Wen YANG; Haiming HU; Hongtao LIU; Xiaobo WEI; Huiyan LIU; Haitian FANG (Shipin gongye ke-ji, 2024)
In order to explore the metabolic process of caffeic acid in vivo, two strains that could metabolize caffeic acid were isolated and screened from human intestinal feces, their strain characteristics were analyzed by cell morphology, 16S rDNA sequence and phylogenetic tree, and the total number of bacteria and pH changes in the process of caffeic acid metabolism in the two strains were studied, and finally the metabolites were determined by thin layer chromatography and high performance liquid chromatography to elucidate the caffeic acid metabolism process. The results showed that the two strains were Staphylococcus xylosus strain and Proteus mirabilis strain. The content of caffeic acid metabolized by Staphylococcus xylosus strain decreased from 0.539 mg/mL to 0.087 mg/mL after 6 h and was completely metabolized after 12 h. However, the content of caffeic acid metabolized by Proteus mirabilis strain decreased from 0.543 mg/mL to 0.352 mg/mL after 6 h, and was completely metabolized after 24 h. Caffeic acid inhibited the proliferation of intestinal bacteria, and the ability of Staphylococcus xylosus strain to metabolize caffeic acid was better than that of Proteus mirabilis strain, and the product of caffeic acid metabolized by intestinal bacteria was m-coumaric acid. The results of the study provided a basis for further research on the interaction between caffeic acid and intestinal bacteria.